Dramatic performance enhancement for large bandgap thick-film polymer solar cells introduced by a difluorinated donor unit. (July 2015) - Li, Zhengke; Lin, Haoran; Jiang, Kui; Carpenter, Joshua; Li, Yunke; Liu, Yuhang; Hu, Huawei; Zhao, Jingbo; Ma, Wei; Ade, Harald; Yan, He
Abstract: We report a large bandgap (1.9 eV) donor–acceptor copolymer (named PffT2-FTAZ) that enables polymer solar cells with a high power conversion efficiency of 7.8%. An important structural feature of the PffT2-FTAZ polymer is a difluorinated donor unit (3, 3′-difluoro-2, 2′-bithiophene, or, ffT2) that introduces several surprising and/or beneficial effects. By comparing PffT2-FTAZ with the analog polymer (PT2-FTAZ) without fluorination on the bithiophene donor unit, it is found that the ffT2 unit effectively lowers the HOMO and LUMO energy levels of the polymer and slightly reduces optical bandgap. It also introduces strong interchain aggregation for the polymer in solution, which leads to a highly crystalline polymer film and reasonably high hole transport mobility. On the other hand, the PffT2-FTAZ: fullerene blend still exhibits a reasonably small polymer domain size suitable for polymer solar cell operation. All these positive factors combined leads to dramatically enhanced performance for the polymer solar cells with the power conversion efficiency increasing from 2.8% for PT2-FTAZ to 7.8% for f PffT2-FTAZ. The high PSC performance of PffT2-FTAZ makes it a promising candidate for high efficiency tandem PSCs. Graphical abstract: Highlights: A polymer PffT2-FTAZ based on fluorinated donor part is designed and synthesized. The PffT2-FTAZ based polymer solar cell achieve 7.8% power conversion efficiency. GIWAXS and AFM etc. are utilized to investigate the fluorination effect. This large bandgap polymer is a potential material for highly efficient tandem cells.